2020
DOI: 10.12659/msm.920445
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Suppresses Apoptosis and Inflammation in Hypoxia/Reperfusion-Exposed Neurons via Wnt Signaling Pathway

Abstract: Background: Cerebral ischemia/reperfusion (I/R) injury contributes to mortality and morbidity in preterm infants. Curcumin has been shown to exert neuro-protective effects in the central nervous system (CNS). The aim of this study was to investigate the neuro-protective activity of curcumin and the possible underlying molecular mechanisms. Material/Methods: A hypoxia/reoxygenation (H/R) protocol was used to simulate I/R injury in vitro. Isolated neonatal neurons were pre-treated with curcumin at serially dilut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
(34 reference statements)
2
21
0
Order By: Relevance
“…A recent study reported that silymarin therapy relieves docetaxel‐induced injury of central nervous system by suppressing inflammation (Yardım et al., 2021). Moreover, the application of curcumin was also found to alleviate damage in neuronal cells by inhibiting inflammation and modulating the Wnt/β‐catenin pathway (Zhou et al., 2020). In this study, inflammatory factors were detected in the serum and brain tissues of rats.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that silymarin therapy relieves docetaxel‐induced injury of central nervous system by suppressing inflammation (Yardım et al., 2021). Moreover, the application of curcumin was also found to alleviate damage in neuronal cells by inhibiting inflammation and modulating the Wnt/β‐catenin pathway (Zhou et al., 2020). In this study, inflammatory factors were detected in the serum and brain tissues of rats.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin possesses several beneficial properties that could make it a suitable candidate for stroke prevention or treatment, including anti-inflammatory, antilipemic, antiaggregant, neuroprotective and epigenetic modulatory activities [ 275 ]. Pre- and posthypoxia treatment with curcumin was found to effectively promote neuroprotection in rat neurons challenged with OGD [ 276 ], in neonatal mice subjected to hypoxic–ischemic brain injury [ 277 ], in MCAO rodents [ 278 , 279 , 280 , 281 , 282 , 283 , 284 ] and in stroke-prone spontaneously hypertensive rats [ 285 ].…”
Section: Polyphenols and Stroke: Results From Preclinical Stroke Mmentioning
confidence: 99%
“…The main active ingredient of turmeric ( Curcuma longa ) is curcumin, which has strong anti-lipidemic, -inflammatory and -aggregating properties, as well as it is an epigenetic modulator and neuroprotective agent [ 77 ]. Neurorestorative properties of curcumin in I/R injury are well documented [ 78 , 79 , 80 ]. Zhou et al showed that curcumin treatment promoted neuronal viability and inhibited apoptosis.…”
Section: Natural Compoundsmentioning
confidence: 99%
“…Zhou et al showed that curcumin treatment promoted neuronal viability and inhibited apoptosis. In in vitro studies (isolated neonatal neurons), curcumin reduced the expression of IL-6, Wnt5a, TNFα, the level of JNK1 phosphorylation, and the NFκB nuclear translocation [ 78 ]. In turn, Li et al observed that curcumin reduces brain edema, disruption of the BBB, and infarct volume in I/R injury through anti-inflammatory, -oxidative and -apoptotic activities.…”
Section: Natural Compoundsmentioning
confidence: 99%
See 1 more Smart Citation